Pengembangan Materi Ajat Teks Berita pada Siswa Kelas VII SMP Negeri 4 Tanjung Morawa - Melly Egidia (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the procedure for the development, form, and feasibility of news text teaching materials for grade VII students. This research uses a research and development (R&D) method with a model developed by Borg and Garl that has been modified by Sugiyono and designed according to the needs and limitations of this research. The stages carried out in this research process are a) potential and problem analysis, b) data collection, c) product design, d) design validation, and e) design revision. Product assessments are carried out by two experts, namely material experts and media experts. The results of the study show that (1) The teaching material of news texts for grade VII students is developed in the form of a book with learning outcomes, namely the ability to write ideas, thoughts, views, directions, or written messages for various purposes logically, critically, and creatively. (2) The results of the validation of material experts show that with an average score of 84% with the criteria of